Overview of homocysteine and its role in disease processes - Aleksandra Kędzia; Michał Bolek; Bartosz Jagieła; Monika Fidyk; Dominika Musialska; Magda Minkiewicz (Quality in Sport)
Homocysteine is a sulfur-containing amino acid formed from the essential amino acid methionine. This metabolism cycle requires vitamin-derived cofactors, pyridoxine for transsulfuration and both folate and cobalamin [1]. In a normal diet there is conservation of the carbon skeleton, and about 50% of the homocysteine formed is remethylated to methionine via steps that require folic acid and vitamin B12. A deficiency of any of these three vitamins leads to modest homocysteine elevation. Why does hyperhomocysteinemia play a vital role in medical practice? It is established that homocysteine elevation is associated with different complications, mainly increased cardiovascular risk [2]. Hyperhomocysteinemia and homocystinuria is connected with occlusive artery disease, especially in the brain, the heart, and the kidney, in addition to venous thrombosis. However the increased level of homocysteine has also an impact on other systems and is connected with osteoporosis, depression, Alzheimer's disease, pregnancy problems, and others. Elevated homocysteine levels occur in both the adult and child population [3].